2014
DOI: 10.1016/j.poly.2014.05.019
|View full text |Cite
|
Sign up to set email alerts
|

To deprotect or not to deprotect: Phosphonate ester versus phosphonic acid anchor ligands in copper(I)-based dye-sensitized solar cells

Abstract: The performances of n-type DSCs containing the heteroleptic copper(I) dyes [Cu(1)(dmbpy)] + and [Cu(2)(dmbpy)] + (1 = ((6,6'-dimethyl-[2,2'-bipyridine]-4,4'-diyl)bis(4,1-phenylene))bis(phosphonic acid); 2 = tetraethyl ((6,6'-dimethyl-[2,2'-bipyridine]-4,4'-diyl)bis(4,1-phenylene))bis(phosphonate); dmbpy = 6,6'-dimethyl-2,2'-bipyridine) have been evaluated to determine whether or not deprotection of the phosphonate ester prior to assembly of the heteroleptic [Cu(L anchor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 30 publications
2
29
0
Order By: Relevance
“…LOT) also leads to differing J SC values. 47 In a bench-marking investigation, 33 Gibson and coworkers included measurements of the performance of p-type DCSs with P1 with a variety of different fabrication methods. The study included electrodes with one screen-printed layer of Solaronix NiO paste and a sintering temperature of 350 1C, leading to values of J SC = 1.57 mA cm À2 , open-circuit voltage (V OC ) = 93 mV, fillfactor (ff) = 32%, and Z = 0.047%.…”
Section: Dsc Performancesmentioning
confidence: 99%
“…LOT) also leads to differing J SC values. 47 In a bench-marking investigation, 33 Gibson and coworkers included measurements of the performance of p-type DCSs with P1 with a variety of different fabrication methods. The study included electrodes with one screen-printed layer of Solaronix NiO paste and a sintering temperature of 350 1C, leading to values of J SC = 1.57 mA cm À2 , open-circuit voltage (V OC ) = 93 mV, fillfactor (ff) = 32%, and Z = 0.047%.…”
Section: Dsc Performancesmentioning
confidence: 99%
“…The process was the same as for the assembly of surfacebound [Cu(4)(1)] + previously reported. 29 Duplicate cells were prepared for each dye and the cell characteristics are shown in Table 2; the data are compared to those of cells containing [Cu(4)(1)] + and to a reference cell containing N719. All cells were fully masked to prevent overestimation of their ]; H atoms omitted and ellipsoids plotted at 30% probability level.…”
Section: Dye Adsorption and Dsc Performancesmentioning
confidence: 99%
“…13,14 This versatile approach allows facile screening of heteroleptic dyes comprising carboxylic or phosphonic acid anchoring ligands with different ancillary ligands, 8,[13][14][15][16][17][18][19] and we have also used the method to assess the different performances of dyes with phosphonic acid or phosphonate ester anchoring domains. 20 To stabilize tetrahedral [Cu(N^N) 2 ] + complexes in which N^N is a bpy or phen (phen ¼ 1,10-phenanthroline) against oxidation to square planar [Cu(N^N) 2 ] 2+ , it is necessary to introduce substituents in the 6,6 0 -or 2,9-positions, respectively, of bpy or phen. 21 For L anchor , we have focused on 6,6 0 -dimethyl-2,2 0 -bipyridines and shown that 1 (Scheme 2) is the most effective anchor of the carboxylic and phosphonic acids screened so far.…”
Section: Introductionmentioning
confidence: 99%